Type I Interferons in Systemic Autoimmune Diseases: Distinguishing Between Afferent and Efferent Functions for Precision Medicine and Individualized Treatment - Chasset, François; Dayer, Jean-Michel; Chizzolini, Carlo (Frontiers in Pharmacology, 2021)
A sustained increase in type-I interferons (IFN-I) may accompany clinical manifestations and disease activity in systemic autoimmune disorders (SADs). Despite the very frequent presence of IFN-I in SADs, clinical manifestations are extremely varied between and within SADs. The present short review will address the following key questions associated with high IFN-I in SADs in the perspective of precision medicine. 1. What are the mechanisms leading to high IFN-I? 2. What are the predisposing conditions favoring high IFN-I production? 3. What is the role of IFN-I in the development of distinct clinical manifestations within SADs? 4. Would therapeutic strategies targeting IFN-I be helpful in controlling or even preventing SADs? In answering these questions, we will underlie areas of incertitude and the intertwined role of autoantibodies, immune complexes, and neutrophils.